ANALISIS PROFIL KETERAMPILAN BERPIKIR KRITIS KONSEP SAINS MAHASISWA PGSD - Elyas Djufri; Devi Septiani; Ahmad Syauqi Hidayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This study aims to analyze the profile of critical thinking skills of PGSD students in learning science concepts. Critical thinking indicators used as a reference in observing critical thinking in this study include: analyzing, predicting, designing ideas. The research carried out includes the type of quantitative research with a descriptive approach. where the data were analyzed by calculating the cognitive ability score with a scoring technique with corrections to guess answers. The research subjects for the third semester students of PGSD UST Yogyakarta are 80 students for the 2021/2022 academic year. The results showed that the critical thinking skills of PGSD students from grades A and B had critical thinking skills with an average (medium) scale of 23.75%, then critical thinking abilities with low criteria of 33.75%. Furthermore, students who have very high critical thinking skills are 6.25%. While those with very low criteria are only 36.25%.